Prototipe Sistem Palang Otomatis Daftar Pencarian Orang (DPO) Berbasis IOT - Ahmad Mutatkin Bakti; Muhammad Arif Rahmad Syahputra (APTIKOM SUMSEL, 2025)
Crimes involving individuals on the Wanted Persons List (DPO) are a serious issue in the modern era. Airports, as hubs of human mobility, play a crucial role in preventing criminal suspects from escaping. However, the high volume of activity at airports necessitates a security system that not only relies on human personnel but also leverages advanced technology. To address this issue, the development of an IoT-based DPO Automatic Barrier System is proposed. This system utilizes components such as ESP8266, a servo motor, a buzzer, and jumper wires, integrated with a Laravel-based website and SQL database. The system operates in real time by detecting National Identification Number (NIK) data linked to the DPO database. The ESP8266 module serves as the primary communication interface, while the servo motor controls the automatic barrier. When an individual listed in the DPO database is detected, the system triggers a buzzer as a warning alarm and activates the barrier to restrict access. The implementation of this system is expected to enhance security and improve monitoring effectiveness at airports for individuals registered in the DPO database.